Hubungan Harga dan Kualitas Pelayanan terhadap Loyalitas Pelanggan di Pasar Kapasan Surabaya - fauzi, moch harun; Cahyono, Hendry (Universitas Negeri Surabaya, 2020)
AbstractThis research was conducted in the Kapasan market in Surabaya, where there are many sellers who sell the same products among other sellers. Attract competition among buyers competing in price and quality of service to attract customers. This study aims to study how the relationship between price and service quality on customer loyalty in the Kapasan Surabaya market. This type of research is quantitative research using data collection through a questionnaire with incidental sampling method. Data analysis used multiple correlation test, partial test (t test), simultaneous test (f test), and coefficient of determination test (R2 test). The results of this study indicate that the price variable has a significant effect on customer loyalty and the service quality variable has a significant effect on customer loyalty. With the test results the coefficient of determination (R2) is at 34.4% meaning that the price and service quality variables play a role of 34.4% on customer loyalty.